Energy Supply Contracting Adoption: Empirical Evidence from the Swiss Market - Sandra Klinke (University of Neuchâtel, Institute of Economic Research (IRENE), 2016)
Energy supply contracting consisting in outsourcing energy-related services is considered as a promising tool to induce investment in energy efficiency and renewable technologies. Yet, energy contracting markets grow slowly and Switzerland is lagging behind. In order to assess whether the potentials are under-exploited, the determinants of energy supply contracting adoption are assessed using a random effects probit model on a dataset of 2,003 accepted and rejected contracts in Switzerland. Results show that the advantages of risk sharing and economies of scale brought by contracting as well as trust towards the supplier and the technology seem determining in the client's choice. The number of interlocutors involved, inducing higher expected adaptation costs, impacts negatively adoption. Less specific contracts involving residential or new buildings are more likely to be signed. The results imply that in order to fully exploit the potentials of contracting, a priority is to clarify to which extent owners can transfer the costs onto the tenants. Information campaigns are still needed to reduce the lack of confidence in energy renewable technologies. This study also provides the suppliers with guidelines to better exploit the market.
Keywords: L24; Q40; 330; Energy service contracting; ESCo; vertigal integration; transaction costs economics; risk sharing; renewable energy